1987
DOI: 10.1002/em.2850100405
|View full text |Cite
|
Sign up to set email alerts
|

Method for selecting exposure levels for the Drosophila sex‐linked recessive lethal assay

Abstract: The use of the Drosophila sex-linked recessive lethal assay for detecting mutagenicity of chemicals is well established. When compounds are tested by feeding adult flies, the National Toxicology Program protocol specifies a 3-day feeding regimen at an exposure level that produces about 30% mortality. Uptake of the test compound is monitored by feeding behavior, amount of excretion, or abdomen size (Woodruff et al: Environ Mutat 7:677-702, 1985). An alternate method for determining uptake is to add radiolabeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We did not see any difference between experimental flies and controls (Supplementary Figure 3A–D). We then measured the food intake of the transgenic flies by incubating them on food mixed with 14 C- labeled -leucine for 48 hours (Thompson and Reed 1987). Ingested 14 C should reflect food consumed.…”
Section: Resultsmentioning
confidence: 99%
“…We did not see any difference between experimental flies and controls (Supplementary Figure 3A–D). We then measured the food intake of the transgenic flies by incubating them on food mixed with 14 C- labeled -leucine for 48 hours (Thompson and Reed 1987). Ingested 14 C should reflect food consumed.…”
Section: Resultsmentioning
confidence: 99%
“…However, at higher concentrations of chemicals food consumption is not proportional to exposure due to feeding rejection [Thompson and Reeder, 1987;Aaron and Lee, 19771. The consequences of feeding rejection in 3 day feeding studies are addressed in the remainder of this communication.…”
Section: Resultsmentioning
confidence: 99%
“…However, the addition of ''C-leucine to the feeding solution resulted in near-linear incorporation of radioactivity into the flies over a 3 day feeding period. Thompson and Reeder [1987] also demonstrated that greater amounts of acrylic acid were consumed from less concentrated test solutions and suggested that toxicity (as determined by lethality) was probably due to starvation rather than chemical toxicity per se.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the total food release, referring to The third approach is the tracer method which quantifies the amount of food intake by directly measuring the amount of the tracer, which is spiked in the food, in the fly bodies. [10][11][12][13][14][15][16][17] The tracers can be either fluorescent dyes or more sensitive radioactive compounds, such as 32 P, 3 H or 14 C. However, the published tracer methods actually measure food retention rather than intake and miss the amount of the tracer excreted out of the flies through feces and eggs in the case of females, which leads to underestimation of the amount of food intake. Using only yeast as the food source and radiophosphorus as the tracer, King and Wilson found that significant amount (~25%) of radiophosphorus was excreted out as feces in a 24-hr feeding.…”
Section: Introductionmentioning
confidence: 99%